EVERDAY LIFE ISSUES OF THE DISABLED WAR VETERANS IN THE POST-WAR UKRAINIAN SSR - HORDIYENKO, Vyacheslav; HORDIYENKO , Halyna (EAST EUROPEAN HISTORICAL BULLETIN, 2025)
The purpose of the research is to elucidate the content of the disabled war veterans’ everyday life in the Soviet reality of the first post-war years, based on the archival documents of the official origin. The methodology of the research is based on the combination of study techniques from various scientific disciplines within the framework of an everyday life history. There have been used diverse concepts from the theory of the Soviet everyday life. The scientific novelty of the research consists in the problem under research formulation, the means and methods of its solution, the research conclusions, and the specificity of the references. Conclusions. The Soviet mentality, in particular its continued existence, is considered to be the problem of modern Ukrainian society. The “Sovietism” hinders the civilizational development of independent Ukraine and is a dangerous factor under the conditions of the Russo-Ukrainian War. Due to a thorough study on the Soviet society using modern techniques of historical research, in particular methods of an everyday life history, it is feasible to solve the above-mentioned problem. There emerged a large social group of veterans with disabilities in the Ukrainian SSR after the end of World War II. A full-fledged historical reconstruction of the post-war everyday life of the Soviet society is impossible without studying the life of this contingent of the war veterans. During the Third Famine in Ukraine, the party and government leadership of the Republic initiated a campaign to reduce the number of veterans with disabilities by manipulating medical and labour check-ups and examinations in order to avoid the deficit in the social security budget. The front-line soldiers with the disabilities were forced to put in a great deal of effort to have their status recognized as “the Disabled of the Patriotic War”, since the status gave the right to the social protection. The administrative pressure was aimed at reducing the percentage of the disabled veterans of Group 2, which caused a typical Soviet everyday life phenomenon – “blat” (favourism and bribes). The survival strategies used by some disabled war veterans also included deception in order to obtain deficit benefits. Numerous disabled war veterans faced a lack of empathy by the society and neglect by the civil servants of their direct duties to provide assistance to veterans in everyday life. Key words: everyday life, disabled war veterans, disability group, favourism, social protection.